Interaction Effect of Sex and Body Mass Index on Gray Matter Volume - Huang, Yufei; Li, Xianjie; Jackson, Todd; Chen, Shuaiyu; Meng, Jie; Qiu, Jiang; Chen, Hong (Frontiers in Human Neuroscience, 2019)
Objective: Few studies have investigated sex differences in brain structure associated with body mass index (BMI), and the related findings are inconsistent. In this study, we aimed to investigate the effect of sex × BMI interactions on gray matter volume (GMV), and to determine the implications of any structural differences. Methods: The final sample comprised 653 participants (449 women) who were assessed using voxel-based morphology analysis of T1-weighted magnetic resonance images. We used the voxel-based morphometry (VBM) to build a multiple regression model to explore the association between BMI and GMV, and used analysis of variance (ANOVA) to explore the BMI × sex interaction on GMV. A subset of 410 participants (291 women) underwent whole brain resting-state functional connectivity (rsFC) analysis to investigate sex differences in the seed (interaction) region. The cluster with a significant effect in the previous ANOVA analysis was used as a seed. Results: A significant BMI × sex interaction was observed in the left anterior cingulate cortex (ACC), while GMV was negatively correlated with BMI in men but not in women. The rsFC between the left ACC and the caudate was lower in men than in women. Within the entire sample, the insula, caudate, and medial frontal cortex activities were negatively correlated with BMI while the cerebellum and postcentral gyrus activities were positively correlated with BMI. Conclusions: Our findings address the interaction effect of BMI and sex on GM alterations. We found that the GMV in men seemed to be more likely to change with BMI than women, and the left ACC may be the reason for the increase in BMI of men, but not women.